SINTASAN DAN PERTUMBUHAN TRANSPLANTASI KARANG HIAS ACROPORA SP DI DESA TONYAMAN, KECAMATAN BINUANG, KABUPATEN POLEWALI MANDAR - Haris, Abdul; Rani, Chair; Tahir, Akbar; Burhanuddin, Andi Iqbal; Samawi, Muh. Farid; Tambaru, Rahmadi; Werorilangi, Shinta; Arniati, Arniati; Faizal, Ahmad (Jurnal Ilmu Kelautan SPERMONDE, 2017)
Culture of ornamental corals applying transplantation technique was aimed to know the successful of this transplantation technique in the ornamental coral culture based on its growth and survival rate of various coral fragments. The location of the medium settlement was in the western side of the waters of Tonyaman Village, Binuang Subdistrict, Polewali Mandar Regency with 3-4 meter depth during low tide. One of coral species i.e. Acropora  sp with 48 fragments was put on 4 transplantation tables. During the experiment, cleaning of fungi and biofouling at the transplant tables and the culture tables. Measurements of the absolute growth and survival rate were done at the 21st day using calliphers and numbers of dead and live fragments were counted directly. Coral transplantation workshop for ornamental coral culture was attended by 4 fisherman groups with total 23 participants. This event was understood by the training participants from the seed selection to the monitoring. Number of coral fragment cultured was 48 fragments obtained from one of stony corals (Scleractania), i.e. Acropora  sp. The range of survival rate that has been cultured for 21 days was adequately high i.e. 91.7 – 100 %. The highest survival rate was observed at the transplant table B, i.e. 100%, whereas, the table A, C, and D were 91.7 %. Average absolute growth of the coral Acropora  sp cultured during this study were ranged from 4.2 – 4.9 mm/month. Aaverage absolute growth was found at table transplant B and C, while the lowest value was observed at the transplant table D.Keywords: cultivation, ornamental coral, transplantation technique, Tonyaman